THE STUDENTS’ DIFFICULTIES OF SMP NEGERI 1 LHOK NIBONG ACEH TIMUR IN MASTERING READING COMPREHENSION - Teuku Mahmud; Sariakin Sariakin (Jurnal Real Riset, 2023)
Reading is one of language skill that is not easy to be mastered by students. The students always get difficulties to master reading comprehension thus they do not master reading skill. The aims of this research are to find out the difficult factors of reading comprehension that are encountered by students of SMP Negeri 1 Lhok Nibong Aceh Timur and to find out the most difficult factors that the students of SMP Negeri 1 Lhok Nibong Aceh Timur face in mastering reading comprehension. This research is conducted by using quantitative method and research design used is a quantitative description. The population of this research is all eight grade students of SMP Negeri 1 Lhok Nibong Aceh Timur. The total subjects of this study is 96 students who are composed of for classes; VIII1, VIII2, VIII3, and VIII4. Meanwhile, the sample of this research was all students who were taken from the four classes. Thus, the technique used in taking sample was total sampling. Therefore, the total sample of this research was 96. The difficult factors of reading comprehension that are encountered by students of SMP Negeri 1 Lhok Nibong Aceh Timur are: difficulties in comprehending word or vocabulary, difficulties in comprehending sentence, difficulties in comprehending paragraph, difficulties in comprehending whole selection or content of a text, and the other factors that make the students get difficulties in mastering reading comprehension such as such difficult to find main idea, to find the plot of a text, to find the kinds of texts, to understand English structure, and no dictionary.Key Words: Difficulties, Mastering, Reading Comprehension